2020
DOI: 10.1159/000508619
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Near-Infrared Light in an Animal Model of CI Surgery

Abstract: <b><i>Introduction:</i></b> The preservation of residual hearing has become an important consideration in cochlear implant (CI) recipients in recent years. It was the aim of the present animal experimental study to investigate the influence of a pretreatment with near-infrared (NIR) light on preservation of sensory hair cells and residual hearing after cochlear implantation. <b><i>Methods:</i></b> NIR was applied unilaterally (15 min, 808 nm, 120 mW) to 8 guinea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Overall, there was a trend toward benefit from PBMT in animal studies, irrespective of delivery method, wavelength and power used or the animal species treated. Audiological outcomes improved in all 16 animal studies following PBMT compared to no PBMT, with statistically significant improvement stated in 11 studies 12,13,19,20,22–27,29 . In the single human study included, no statistically significant effect of PBMT on hearing was detected 7 .…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Overall, there was a trend toward benefit from PBMT in animal studies, irrespective of delivery method, wavelength and power used or the animal species treated. Audiological outcomes improved in all 16 animal studies following PBMT compared to no PBMT, with statistically significant improvement stated in 11 studies 12,13,19,20,22–27,29 . In the single human study included, no statistically significant effect of PBMT on hearing was detected 7 .…”
Section: Resultsmentioning
confidence: 87%
“…Ten studies assessed ABRs and showed an improvement in hearing, and inner ear elements on histology when compared to the placebo or non‐treatment group 18,20,22–25,27,29,30,31 . Hearing was better preserved or maintained in the PBMT group versus non‐PBMT group in most studies 12,13,18,20,22,23,25,26,28–31 . The effect of PBMT in reducing inflammation was also supported through histology and immunohistochemistry findings, such as increased SGNs, hair cells, and ATP 18,23,25,28 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…16,17 Due to the beneficial effects of LLLT, it is widely used as a treatment approach in a variety of diseases. [18][19][20][21] One of the important effects of laser radiation is the inhibition of apoptosis and regulating cell viability. 22 It was shown that low-power laser radiation caused the sharp expression of the B-cell lymphoma 2 (Bcl-2) antiapoptotic gene.…”
Section: Inflammatory Responses In the Pathogenesis Of Msmentioning
confidence: 99%